Decoding systemic risks across commodities and emerging market stock markets - Fahmi Ghallabi; Ahmed Ghorbel; Sitara Karim (Financial Innovation)
Abstract This study explores correlations and risk spillovers, essential concepts for financial risk management, among commodities (crude oil, gold, and a global commodities index) and emerging stock markets. Using the Asymmetric Dynamic Conditional Correlation–Conditional Value-at-Risk (ADCC-CoVaR) model and a bootstrapped Kolmogorov–Smirnov (KS) test, we analyze the period from December 30, 2005, to February 28, 2024, examining correlations, downside and upside risk spillovers, and highlighting the effects of major events such as the global financial crisis of 2008, the COVID-19 pandemic, and the Russia-Ukraine war. The results show heightened correlations during crises and significant risk spillovers across market pairs, with downside risks often outweighing upside risks. Gold displays minimal risk spillover, highlighting its unique role as a haven asset. We find that spillovers between gold, global commodities, and stocks increased during the pandemic and the Russia-Ukraine conflict, while those involving crude oil remained stable. These findings provide valuable guidance for portfolio managers in navigating volatile markets.